Phytochemical Screening and InVitro Determination of Antioxidant Potential of Methanolic Extract of Streospermum Chelonoides - Meena Afroze Shanta, Taksim Ahmed & , Mohammad Nasir Uddin & , Senjuti Majumder, Md. Solayman Hossain, Md. Sohel Rana (Journal of Applied Pharmaceutical Science, 2013)
Plant derived phytochemicals consisting of phenols and flavonoids possess antioxidant properties, eventually renders a lucrative tool to scavenge reactive oxygen species (ROS). Current study evaluates the preliminary phytochemical screening and antioxidant activity of methanolic extract of bark and leaf of Stereospermum chelonoides. Thus, various in vitro assay strategies were implemented to evaluate antioxidant potential of Stereospermum chelonoides, using DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging assay, ferric reducing antioxidant power (FRAP), total antioxidant capacity, determination of total phenol and flavonoid contents. Preliminary phytochemical study revealed the presence of alkaloid, carbohydrate, glycoside, flavonoid, steroid and tannin. In DPPH radical scavenging assay, the fraction showed significant antioxidant activities in the assay compared to the reference ascorbic acid in a dose dependent manner. The IC50 value of the crude methanol extract of bark and leaf was 53.99±3.25 µg/mL and 84.73±4.02 µg/mL, respectively, whereas IC50 value for the reference ascorbic acid was 14.56±0.24 µg/mL. Moreover, profound total antioxidant activity was observed for bark (309.88±1.03 mg/g equivalent to ascorbic acid) as well as leaf (147.09±1.79 mg/g equivalent to ascorbic acid) at 200 µg/mL extract concentration. Furthermore, extract showed good reducing power capability in both bark and leaf fraction. Total phenol content for the bark was 574.82 mg/g equivalent to gallic acid and for leaf was 189.86 mg/g. For bark, the total flavonoid content was found 55.82 mg/g equivalent to quercetin and for leaf it was 49.44 mg/g.
Keywords: Stereospermum chelonoides, antiox